The Prevalence of Alcohol in Road Traffic Accidents Fatalities in Central Serbia - Živana Slović; Katarina Vitošević; Danijela Todorović; Mihailo Jovanović; Filip Mihajlović; Dragan Milovanović; Olgica Mihaljević; Miloš Todorović (Iranian Journal of Public Health, 2022)
No Abstract